The Dentoalveoler Effect Of Trıple Combınatıon Of Actıvator, Occıpıtal Headgear, And Vertıcal Chın-Cap On Treatment Of Open-Bıte Cases - Meliha Rübendüz; Zahir Altuğ (Galenos Yayinevi, 1997)
This study was held on totally 68 lateral cephalograms and hand-wrist radiograms of 34 individuals. Nineteen of individuals were treatment group with skeletal and dental open-bite characteristics (13 girls, 6 boys). Fifteen of 34 individuals were nontreatment control group with skeletal and dental open-bite characteristics (7 girls, 8 boys). The materials of this study were obtained from the individuals at the beginning and at the end of treatment and controls. The effects of the treatment were investigated on these radiograms by means of 41 dental measurements. As a resuit, lower and upper incisors retractions were found to be effective in openbite treatment.